Faedah Pelaksanaan Sistem Pengurusan Kualiti Berteraskan Syariah MS 1900 Di Darul Quran, JAKIM - Muhammad Firdaus Zakaria; Siti Arni Basir; Osman Md Rasip (USIM Press, 2024)
Vol. 6 No. 3 (2021): Special Issue